From single SQUID to superconducting quantum arrays - Kornev, V.K.; Kolotinskiy, N.V.; Sharafiev, A.V.; Soloviev, I.I.; Mukhanov, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Superconducting quantum arrays (SQAs) capable of providing highly linear voltage response to magnetic signal and high dynamic range have been suggested and developed. Base elements of the arrays, quantum cells, were devised and studied in detail. Using niobium process, SQAs with different number of the cells and prototypes of the SQA-based broadband active electrically small antennas were fabricated and tested.